Exploring the Multifunctional Neuroprotective Promise of Rasagiline Derivatives for Multi-Dysfunctional Alzheimer’s Disease - Uddin, Md. S.; Kabir, Md. Tanvir; Rahman, Md. Habibur; Alim, Md. Abdul; Rahman, Md. Motiar; Khatkar, Anurag; Al Mamun, Abdullah; Rauf, Abdur; Mathew, Bijo; Ashraf, Ghulam Md. (Current Pharmaceutical Design, 2020)
Alzheimer's disease (AD) is a chronic, age-related, and irreversible brain disorder that typically develops slowly and gets worse over time. The potent auspicious drug candidate for the treatment of AD is supposed to perform the simultaneous modulation of several targets linked to AD. The new therapeutic approach involves drug candidates that are designed to act on multiple targets and have various pharmacological properties. This trend has triggered the development of various multimodal drugs including TV-3326 (i.e. ladostigil) and M-30 (i.e. a new multitarget iron chelator). TV-3326 combines the neurorestorative/neuroprotective effects of the cholinesterase (ChE) inhibitory activity of rivastigmine with rasagiline (a selective monoamine oxidase-B inhibitor and novel antiparkinsonian agent) in a single molecule. M-30, the second derivative of rasagiline, was developed by combining the propargyl moiety of rasagiline into the skeleton of VK-28 (i.e. a novel brain permeable neuroprotective iron chelator). It has been revealed that both the compounds possess anti-AD effects and therefore, the clinical development is directed to the treatment of this type of neurodegenerative diseases (NDs). In this article, we have reviewed the neuroprotective molecular mechanisms and multimodal effects of TV-3326 and M-30.
Keywords: TV-3326